(3JdNjU GdeaJGMs - (3LdGd GdOjf eMeO Hf YHO GdQMef Hf YeQ GdbRhjfi GdTGaYj GdeYQha HNWjH OeTbs; (3GdScGcj , SQGL GdOjf CHh jYbhH jhSa Hf CHj HcQ Hf eMeO Hf Ydj GdScGcj GdNhGQRej GdMfaj, GdScGcj,J (B626 (3g` s ((3YHO GdQMef Hf GdMSf Hf bGSe GdMfai s)
(3ChdgG (B:s
(3CeG HYO adeG cGf Yde GdHdGZI hJhGHYgG ef GLd GdYdhe hjcTa Yf hLhg GdGYLGR ai fXe GdbQGf hcGf GdbSe GdKGdK ef eaJGM GdYdhe GdPi UfYg CHh jYbhH jhSa GdScGci GdhJ eNJUQkG GJVef eG ajg ef GdbhGYO hjTJed Ydi eG jMJGL ajg ef GdGeKdI s
(3BNQgG (B:s
(3hLejY ahGJM GdShQ hNhGJjegG hGQGOI Ydi GMSf GdhLhg hGcdegG jXgQ Pdc HGdJCed eY GdJPcjQ deG JbOe hGddg Gdehab ddUhGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdHdGZIs